2017
DOI: 10.1080/20009666.2017.1407210
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with short recurrence-free survival in completely resected colon cancer

Abstract: Background: Several factors could affect disease recurrence in surgically resected colon cancer. While the role of certain factors such as cancer stage and grade is well established, the role of other factors (e.g., histological subtypes) is yet to be determined. Objective:Therefore, we conducted a study to evaluate the impact of several factors in recurrence-free survival (RFS) in patients who were disease free following surgical resection of the colon cancer. Design/Methods: Data were collected for patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The local recurrence was verified in 19.2 % of cases, lower than reported after curative resection, which can reach 31 % (Alnimer et al, 2017). There is evidence that this is associated with vascular or lymphatic permeation to a number of resected lymph nodes less than 12, as well as the type of resection (R1 and R2) (Kojo et al, 2017).…”
Section: Discussionmentioning
confidence: 90%
“…The local recurrence was verified in 19.2 % of cases, lower than reported after curative resection, which can reach 31 % (Alnimer et al, 2017). There is evidence that this is associated with vascular or lymphatic permeation to a number of resected lymph nodes less than 12, as well as the type of resection (R1 and R2) (Kojo et al, 2017).…”
Section: Discussionmentioning
confidence: 90%
“…The relationship between the recurrence interval and the use of adjuvant therapy remains unclear in the literature (Ryuk et al., 2014). It is known that adjuvant chemotherapy and tumour stage are variables closely related (Alnimer et al., 2017; Touchefeu et al., 2016) and that is why we opted to study them together. We found that regardless of whether patients received adjuvant chemotherapy, recurrence was more likely in all groups than in the least severe group (TNM I not given chemotherapy).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the 5‐year survival rates for regional and distant stages are 70% and 15% respectively (American Cancer Society 2014; Holmes et al., 2017). Despite the various types of treatment available, the chance of recurrence and metastasis of CRC among patients is high (Alnimer et al., 2017) and it depends on disease stage (Ryuk et al., 2014; Tsai et al., 2009; Zare‐Bandamiri, Fararouei, Zohourinia, Daneshi, & Dianatinasab, 2017). Fifty per cent of patients with stage III disease will experience disease recurrence (Zhang et al., 2016), this occurring within the first 3 years after initial resection in 80% and in 90% of cases within the first 4 years (Maeda et al., 2017; Seo et al., 2013; Tsai et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local recurrence was verified in 19.2 % of cases, lower than reported after curative resection, which can reach 31 % (Alnimer et al, 2017). There is evidence that this is associated with vascular or lymphatic permeation; to a few resected lymph nodes (less than 12); as well as the type of resection (R1 and R2) (Kojo et al, 2017).…”
Section: Novelty Of the Proposalmentioning
confidence: 91%